Augmented Hohmann Transfer for Spacecraft with Continuous-Thrust Propulsion System - Alessandro A. Quarta (Aerospace)
Hohmann transfer is the classical approach used in astrodynamics to analyze the optimal bi-impulsive transfer, from the point of view of the total velocity change, between two circular, coplanar orbits of assigned radius. The Hohmann transfer is characterized by an elliptical trajectory tangent to both circular orbits at the points where the transfer begins or ends and can be used to simply model, in a Kepler problem, a possible optimal transfer of a spacecraft equipped with a high-thrust propulsion system. Recent literature has proposed a sort of extension of the Hohmann transfer to a heliocentric mission scenario, where the total velocity change is reduced compared to the classical result by employing a photonic solar sail operating along the deep-space transfer trajectory. The study of this so-called augmented Hohmann transfer, where the spacecraft uses both two tangential impulses (one at the beginning and one at the end of the flight) provided by a high-thrust propulsion system and the propulsive acceleration (during the flight) provided by a low-thrust propulsion system, is extended in this paper by considering a more general case where the spacecraft moves around a generic primary body and uses, along the transfer, a freely orientable propulsive acceleration vector with constant and assigned magnitude. This scenario is consistent, for example, with the use of a typical electric thruster instead of the photonic solar sail considered in recent literature. In particular, the paper studies the impact of the continuous-thrust propulsion system on the transfer performance between the two circular orbits, analyzing the variation of the total velocity change as a function of the propulsive acceleration magnitude. The procedure, which uses an optimal approach to performance estimation, can be used both in a heliocentric and planetocentric mission scenario and can also be employed to analyze the performance of a spacecraft equipped with a multimode propulsion system.